Mental Health Care Barriers for Women Involved in the Criminal Legal System With Substance Use Disorders: A Qualitative Study - Skogseth, Emma M. (Criminal justice and behavior, 2025)
This study investigated barriers to accessing mental health care among criminal-legal involved women with opioid use disorder (OUD) by triangulating perspectives across affected women (n = 20), criminal legal professionals (n = 10), and substance use disorder (SUD) treatment professionals (n = 12). Themes from qualitative interviews conducted in 2022 identified two primary types of barriers: physical access and stigma. Findings converged regarding challenges associated with accessing mental health care during incarceration and reentry and difficulties accessing timely care. However, while women expressed concern about stigma around seeking mental health medications, some of the professionals expressed stigmatizing views about potential misuse of medications. These findings highlight a need for system-level changes in correctional facilities to reduce stigma and bolster well-being and SUD treatment outcomes among criminal-legal involved individuals with dual diagnoses. Future work should strive to expand the literature around interconnected issues associated with concurrent OUD and mental health challenges.